Common genetic and clinical risk factors: association with fatal prostate cancer in the Cohort of Swedish Men - Huynh-Le, M-P; Karunamuni, R; Fan, CC; Thompson, WK; Muir, K; Lophatananon, A; Tye, K; Wolk, A; Håkansson, N; Andreassen, OA; Dale, AM; Seibert, TM; et al. (Springer Nature, 2021)
Background Clinical variables—age, family history, genetics—are used for prostate cancer risk stratification. Recently, polygenic hazard scores (PHS46, PHS166) were validated as associated with age at prostate cancer diagnosis. While polygenic scores are associated with all prostate cancer (not specific for fatal cancers), PHS46 was also associated with age at prostate cancer death. We evaluated if adding PHS to clinical variables improves associations with prostate cancer death.